BIOCHEMICAL CONSTITUENTS OF AMNIOTIC AND ALLANTOIC FLUIDS IN CHITAL DEER (AXIS AXIS) - MURUGAVEL, K; SALAM, D. ABDUL; BARATHIRAJA, S; THANISLASS, J; ANTOINE, D; RAJU, M S (The Indian Journal of Animal Reproduction, 2023)
The present study was undertaken to compare the values of some biochemical profiles of allantoic and amniotic fetal fluids among three trimesters of gestation period in Chital deer hinds. The level of glucose declined relatively from first trimester to third trimester of gestation in both amniotic and allantoic fluids. The glucose concentration was higher in the allantoic fluid than amniotic fluid. The total protein level was found to increase in amniotic fluid and decrease in allantoic fluids as gestation advances. The amount of total protein in a!lantoic fluid was higher than amniotic fluid. There was no significant difference in the urea level in amniotic fluid during different stages of gestation. Urea and creatinine concentrations in allantoic fluid were higher than in the amniotic fluid. The sodium concentration was significantly higher in amniotic fluid when compared to allantoic fluid. Concentration of calcium was significantly higher in allantoic fluid compared to amniotic fluid. There was no significant difference in the level of phosphorus between amniotic and allantoic fluid.